2022
DOI: 10.1039/d2sm01141g
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical advances in molecular bottlebrushes and comblike (co)polymers: solutions, gels, and self-assembly

Abstract: This review presents an overview of recent theoretical developments in increasingly complex polymer systems comprising comb-like or bottlebrush building blocks and compares theoretical predictions to experimental results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 136 publications
0
8
0
Order By: Relevance
“…A molecular brush is envisioned as a wormlike chain with thickness D (which is end-to-end distance of the side chains normally to the backbone), spacer end-to-end distance h , effective contour length , and persistence length . In the framework of scaling model [ 36 , 42 ], the strand thickness D and spacer end-to-end distance h are specified by the balance between the elastic stretching of side chains and spacers, and repulsive monomer-monomer interactions in the cylindrical layer around the main chain, to give …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A molecular brush is envisioned as a wormlike chain with thickness D (which is end-to-end distance of the side chains normally to the backbone), spacer end-to-end distance h , effective contour length , and persistence length . In the framework of scaling model [ 36 , 42 ], the strand thickness D and spacer end-to-end distance h are specified by the balance between the elastic stretching of side chains and spacers, and repulsive monomer-monomer interactions in the cylindrical layer around the main chain, to give …”
Section: Resultsmentioning
confidence: 99%
“…Combining branched architecture with temperature-, pH-, and light-responsive functions in the main and side chains of molecular brushes opens new opportunities for smart material design [ 17 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Since properties of the constituent macromolecules play a governing role in functions of the materials, analytical theories [ 36 , 37 , 38 , 39 , 40 , 41 , 42 ] and self-consistent field numerical [ 43 ] approaches; and coarse-grained computer simulations [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ] of branched polymers have been used to corroborate the relationships between macromolecular architecture and experimentally accessible properties of melts, solutions, and thin films comprising molecular brushes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complex synthetic polymer architectures (topologies) have garnered interest over the years due to their ability to capture intricate properties found in nature. A particularly interesting one is bottlebrush polymers, which contain polymer backbones with densely grafted polymeric side chains, similar to the topology of proteoglycans. The densely packed side-chains prevent entanglement of these macromolecules, influencing properties such as elasticity and domain size in solid-state materials and nanoscopic size and shape in solution. As a result, bottlebrush polymers have many potential applications, including as elastomers with unusual properties, as carriers in biomedicine/drug delivery, and as photonic crystals, and semiconductors. Tuning properties in these materials is achieved through adjusting the backbone and side-chain degree of polymerization ( N bb and N sc , respectively), as well as grafting density ( z , the fraction of monomer units that contain side-chains) . However, control over these structural features of the resulting polymers is sometimes lost at high N bb or N sc , especially when z is near 1.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, the focus of the research was mainly to fundamentally understand the structure of bottlebrush chains and how the structural parameters affect the morphology and mechanics of bottlebrushes in the melt or in the network. 3,[12][13][14][15] These theoretical understanding of bottlebrush chains are continuously developing as, for instance, it has been recently reported that in bottlebrushes with an incompatible backbone and side chains, i.e. composites, the backbone folds into a cylindrical core to reduce the interfacial free energy.…”
Section: Introductionmentioning
confidence: 99%